Analisis Pengendalian Persediaan Bahan Baku Kertas Menggunakan Metode Material Requirement Planning (MRP) di Perusahaan Manufaktur - Priyatna, Thalita Assyifa Dwi; Vikaliana, Resista (TIN: Terapan Informatika Nusantara, 2024)
PT ABC is a manufacturing company that has been operating for more than 30 years in the packaging industry such as paper bags, inner boxes, corrugated carton boxes, rigid boxes, and pulp molds. Based on several materials needed in the production process, duplex paper is the one that has the most problems due to the nature of the material being easily damaged and also orders being made more frequently than other materials. Delays in deliveries from suppliers, the quality of raw materials being below standard so they cannot be used for production, and unexpected spikes in customer demand are the main problems faced by PT ABC. This often results in excesses and shortages of raw materials in the company and makes total inventory costs unstable. In order to avoid wasteful inventory costs and optimize the amount of inventory, proper raw material inventory control is needed. One effective method for implementing raw material inventory control is Material Requirement Planning (MRP) using Economic Order Quantity (EOQ), Point Order Quantity (POQ) and Lot for Lot (LFL) techniques. Apart from that, forecasting is also needed to reduce the level of uncertainty in the future by providing estimates of what might happen. So, this research aims to determine the best forecasting method and the most optimal lot sizing technique so that the company's total inventory costs are more efficient. From the data processing that has been carried out, the Moving Average method is the best method because it obtains the smallest error value, while the LFL lot sizing technique is the most efficient with the smallest total inventory costs of IDR 5,040,000 per year compared to the EOQ technique of IDR 31,185,794 and POQ amounting to IDR 23,042,365.